2021
DOI: 10.1111/bcp.14757
|View full text |Cite
|
Sign up to set email alerts
|

Atropine‐induced toxicity after off‐label sublingual administration of eyedrop for sialorrhoea treatment in neurological disabled patients

Abstract: Sialorrhea is a troublesome and disabling symptom defined by the unintentional loss of saliva from the mouth, usually associated with swallowing disorders. Today there is no consensus about the management of sialorrhoea, but off-label use of ophthalmic atropine eyedrop administered sublingually may offer benefits, despite limited safety data. We report 2 cases of atropine overdose after sublingual administration illustrating that atropine can expose to severe adverse effects when administered sublingually. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This clinical trial showed that atropine gel (0.1 mg) after topical oral administration did not result in any local or systemic adverse events. However, systemic side effects like tachycardia, fever, tremors, and restlessness may be expected with atropine gel with increased dose 24 . Although the self‐administration of gel to the oral mucosa may introduce variability between participants, the interindividual trends remained consistent.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This clinical trial showed that atropine gel (0.1 mg) after topical oral administration did not result in any local or systemic adverse events. However, systemic side effects like tachycardia, fever, tremors, and restlessness may be expected with atropine gel with increased dose 24 . Although the self‐administration of gel to the oral mucosa may introduce variability between participants, the interindividual trends remained consistent.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to available anticholinergic agents, off‐label use of atropine eye drops to treat sialorrhea is mainstay therapy in institutions across the world 15–22 . However, this off‐label treatment is limited by the need for frequent administration due to lack of retention on oral mucosa, 18 incidence of dosing and medication errors, 23 and systemic side effects, such as tachycardia, fever, tremors, and restlessness 24 . Several case reports described that the dosing and medication errors with atropine eye drops were due to accidental ingestion of the entire contents of the atropine eye drop bottle by the patients 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…An overdose of atropine leads to symptoms that include nausea, vomiting, dry mouth, mydriasis, blurred vision, fever, rash, tachycardia, confusion, urinary retention, hallucinations, and delirium. 10 We suggest that while decreasing the intravenous atropine dose, a gradual increase in the sublingual administration of atropine eye drops (0.5 mg per drop) may be necessary until only sublingual atropine is required. The anticipated adverse effects of atropine eye drop sublingual administration were not observed in this patient.…”
Section: Discussionmentioning
confidence: 98%
“…Sialorrhea, defined as drooling or the excessive flow of saliva from the mouth, is observed in patients with cerebral palsy, amyotrophic lateral sclerosis, and Parkinson's disease. 10 The treatment of sialorrhea is often the off-label use of atropine eye drops administered sublingually. The novelty of our patient's treatment is that sublingual administration of atropine eye drops was used for prolonged OP poisoning symptoms, and the patient had a good outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation